The Suggestive Magic of Van Gogh in Heidegger's Interpretation - Busku, Szilvia (Acta Cultura et Paedagogicae, 2024)
The present paper brings to the fore the unforeseen fit and harmony of Heidegger's artwork with the world, and supports the above statement with relevant details. On the one hand, it touches on the Heideggerian conception that takes the interpretation of art in a different direction, making it clear by eliminating established notions of appearance, and on the other hand, it outlines how Heidegger interprets Van Gogh's painting A Pair of Shoes, which has become particularly famous because of the controversy surrounding it. I will present Heidegger's highly perceptive interpretation of the original peasant world through the lens of reviews by Frederic Jameson, Meyer Schapiro and Jacques Derrida.